The genus Chloris Sw. (Poaceae: Chloridoideae) in Mexico - Cerros-Tlatilpa, Rosa; Siqueiros Delgado, María Elena; Skendzic, Elizabeth M. (Instituto de Ecología, A.C., 2015)
Twelve species of Chloris from Mexico are recognized in this study. Five are cosmopolitan species, five are American, two are restricted to Mexico and USA, one occurs in America and Australia, whereas C. truncata is recorded for the first time in Mexico. Chloris barbata, C. gayana, and C. virgata are considered invasive species in the country. An identification key, descriptions and distribution maps are included. The genus occupies a variety of habitats, growing from disturbed zones to conserved areas.